Active site structure study of Cu/Plate ZnO model catalysts for CO2 hydrogenation to methanol under the real reaction conditions. Issue 37 (April 2020) - Sun, Yuhai; Huang, Chunlei; Chen, Limin; Zhang, Yujun; Fu, Mingli; Wu, Junliang; Ye, Daiqi
Graphical abstract: Highlights: Cu/Plate ZnO model catalysts with relatively high CH3 OH yield under real conditions were constructed. Catalyst microstructures can be identified and controllably tuned through the increasing of Cu content. Catalyst microstructures transformation was revealed by SEM (mapping), XRD, H2 -TPR and in situ Raman spectra. The interface caused by migrated ZnO x covered Cu nanoparticles has high reactivity for both CO2 conversion and CH3 OH production. Abstract: Plate-like ZnO, dominantly exposed (002) polar facet, supported Cu catalysts were prepared by impregnation method as model catalysts for CO2 hydrogenation to methanol under the real reaction conditions. The catalysts were thoroughly characterized by Scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), in situ Raman spectra, Temperature-programmed reduction (H2 -TPR) and CO2 Temperature-programmed desorption (CO2 -TPD). Catalyst microstructures can be obviously tuned through the increasing of Cu content, interface constituted by Cu-Plate ZnO direct contact, interface constituted by Cu (on ZnO) covered by migrated ZnO x and interface constituted by isolated Cu nanoparticles covered by migrated ZnO x . These microstructures displayed different catalytic performance for CO2 hydrogenation to methanol; among them, interface caused by the migrated ZnO x covered Cu nanoparticles should play vital roles for methanol production.